(untitled) (Indian Journal of Animal Production and Management, 2013)
The dairies having only cows were have the highest number of cross-bred J x S followed by HF x S, HF and J x H and in the mixed herds only. Similarly amongst the indigenous breed have more numbers of Shiwal cows were kept by the dairies having cattle only and mixed herd. The avergae numbers in the II and III groups were estimated as 32.60 and 7.55 for HF x S, 52.67 and 11.35 for J x S, 3,48 and 1.30 for J x H, 3.26 and 48.56 and 14.22 for Sahiwal, 3.33 and 2.47 for Haryana, and 18.12 and 8.18 for deshi Gangatiri cattle respectively. As stated earlier, being a dairy breed the Sahiwal and the cross of this either HF or Jersye is commonly reared by most of the dairies having buffaloes only i.e. I group and the III groups comprising of both the cattle as well as buffaloes include the average numbers as 41.79 and 21.70 respectively. Thus, in the mixed herd more numbers of cows including both, different cross-breeds and indigenous breeds of cattle were kept while the total number of buffaloes was lesser than the cows, indicating a significant difference between the groups.